ToF‐SIMS analysis of diadenosine triphosphate and didadenosine tetraphosphate using bismuth and argon cluster ion beams. (10th April 2014) - Shon, Hyun Kyong; Cho, Young‐Lai; Lim, Choung Su; Choi, Joon Sig; Chung, Sang J.; Lee, Tae Geol; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; Lee, Tae Geol; Lee, Jae Cheol; et al.
<x xml:space="preserve">Abstract</x> In the past few decades, research has shown diadenosine polyphosphates (ApnA) to be a family of intercellular and intracellular signaling molecules that play a key role in biological and pharmacological activities. ToF‐SIMS, recently shown to be a promising technique to analyze metabolites in biological samples due to its high sensitivity and specificity, was employed to analyze mixed diadenosine triphosphate (Ap3A) and diadenosine tetraphosphate (Ap4A) spiked in HeLa cell lysates by using bismuth and argon cluster ion beams. The molecular ion signals of Ap3A and Ap4A in the cell lysates were stronger when using an argon cluster ion beam than when using a bismuth cluster ion beam, although the detection limits of both molecules were the same. Using a correlation curve to indicate the molecular signal intensities and concentrations, the amount of Ap3A and Ap4A molecules in HeLa cell lysates could be quantified in the concentration range of 0.1 mM to 10 mM for Ap3A, and 5 mM and 20 mM for Ap4A. We believe that ToF‐SIMS analysis could be a powerful technique to detect important metabolite molecules such as ApnA for biomedical applications, without the need for a separation process. Copyright © 2014 John Wiley & Sons, Ltd.